Bank profit in Malaysia from perspective of profitability analysis / Nur Syafika Mohd Zainal Abiddin - Mohd Zainal Abiddin, Nur Syafika (Faculty of Business Management, 2017)
The study is about how the factors influencing the profitability performance of a Malaysian bank. The study evaluates the profitability performance of a bank by using their capitalization ratio, liquidity ratio and bank size thus profitability is measure by looking into the bank profitability (ROA). This research is aims to study the factors of profitability (ROA) towards performance of banks in Malaysia. The dependent variable use is Bank Profitability while the independent variable which is capitalization, bank size, and liquidity. Data are gathered from Emerald and financial ratio are collected from bank‟s annual report in Data Stream and Bank scope, which covering a period between 2007 until 2015. This study uses panel regressions to determine the relationship of the variable. Data that have been analyse using the Econometric 8.0 while this study has choose Panel Data Regression Models.